Use of Databases to Manage Sales Results Data at the KDH Sancang Coffee Shop - Agung Prayudha Hidayat Hidayat; Apristio Faza Ridhar Rahman; Azka Khairani Marisda; Ghailan Arhab; Nayla Cahya Kamila; Rafiq Rizki Prabowo; Sesar Husen Santosa (Batrisya Education, 2024)
Technological advances allow entrepreneurs to manage sales data efficiently. Governance management in micro, small and medium enterprises is often an obstacle to the continuity and development of the business. Based on interviews conducted, at KDH Sancang Coffee Shop, data management still uses Microsoft Excel, which sometimes makes it difficult for users to access the desired data. This research recommends using Microsoft Access to create a secure and organized sales database. This solution helps overcome data duplication problems and improve data accessibility and security. Based on the research results, the process of creating a database for sales results includes the creation of item and sales data tables, one to one relationship, Query total sales results, and Form Design for easy data access. This research activity aims to enable micro, small, and medium-sized enterprises to effectively organize their financial records, including providing owners with the necessary tools to manage their business finances more efficiently. The results showed that the use of Microsoft Access increased the efficiency of managing monthly sales data at KDH Sancang Coffee Shop which is expected to facilitate monthly sales evaluation activities at the coffee shop.